The Effectiveness Of Telemedicine To Improve Quality Of Life For Patients In The COVID-19 Pandemic - Nutrisia Aquariushinta Sayuti; Nur - Atikah (Poltekkes Kemenkes Surakarta, 2022)
Background: COVID-19 delivers the effects of health services in form. Health services began to enforce health protocols, especially social distancing. Medical consultations carried out during medical visits become remote medical consultations by maximizing electronic health technology (e-health), telehealth, and/or telemedicine. The use of health technology has increased research on telemedicine’s effectiveness on patients' health-related quality of life (HRQoL). The aim of this study is to analyze the effectiveness of telemedicine in improving the quality of life of chronic disease patients that require regular visits to health providers during the COVID-19 pandemic during Covid-19 Pandemic. Methods: The research was descriptive. A systematic review with source data from Pubmed, ScienceDirect, and Sage databases with the keyword